MENINGKATKAN EFEKTIFITAS HASIL BELAJAR SISWA MELALUI SISTEM PENDIDIKAN 4 JAM PEMBELAJARAN PADA JENJANG SMA - Vitria Indriyani Setyaningsih; Nabila Jayshi Syah Putri; Oldri Permata Sari; Miftakhul Huda (Jurnal Pendidikan (Teori dan Praktik), 2020)
Full Day school is an education system that carries out a full-day learning process that starts from 6:45 until 3:00. Behind the advantages of the 2013 curriculum that allows productive students to study in school for a long time. The system also has a weakness that is quite influential on students that is not effective in providing rest time for the brain. The system might cause students to become bored, tired and feel burdened because they have to study for the duration of that long. This study aims to discuss how the planned forms of innovation provide solutions to the ineffectiveness of the education system in the 2013 curriculum and about how the 4-hour learning innovation system in one day as a form of the effectiveness of learning outcomes. This system has a disadvantage that is quite influential on students that is not effective in providing rest time for the brain. The system might cause students to become bored and feel burdened because they have to study for the duration of that long. The research method used is descriptive qualitative by examining several data sources and analyzing and comparing existing innovations with previous research. The development of this innovation is that it can reduce the burden of students' minds from the 2013 curriculum education system by using a 4-hour learning design to focus students on learning some subjects they want to master, it is supported by holding reflections on student learning outcomes so that teachers can evaluate how development learners learn from the teaching and learning process that has taken place.